2017
DOI: 10.1155/2017/7213043
|View full text |Cite
|
Sign up to set email alerts
|

Four Major Factors Contributing to Intrahepatic Stones

Abstract: Intrahepatic stone is prevalent in Asian countries; though the incidence declines in recent years, the number of patients is still in a large quantity. Because of multiple complications, high recurrence rates, serious systemic damage, and a lack of extremely effective procedure for the management, it is more important to find out the etiology and pathogenesis of intrahepatic stones to prevent the disease from happening and developing rather than curing. A number of factors contribute to the development of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 21 publications
0
32
1
Order By: Relevance
“…The reported average morbidity is 0.6%-1.3% in the west, even though Asian studies have shown a trend for reduced prevalence. [2] Multiple etiological factors including diet, nutrition, biliary tract abnormalities, recurrent bacterial and parasitic infections, and immune status have been implicated. [2] In general, affected patients have a prolonged history of recurrent abdominal pain, fever, chills, and jaundice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported average morbidity is 0.6%-1.3% in the west, even though Asian studies have shown a trend for reduced prevalence. [2] Multiple etiological factors including diet, nutrition, biliary tract abnormalities, recurrent bacterial and parasitic infections, and immune status have been implicated. [2] In general, affected patients have a prolonged history of recurrent abdominal pain, fever, chills, and jaundice.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Multiple etiological factors including diet, nutrition, biliary tract abnormalities, recurrent bacterial and parasitic infections, and immune status have been implicated. [2] In general, affected patients have a prolonged history of recurrent abdominal pain, fever, chills, and jaundice. Intrahepatic calculi occur proximal to the confluence of the right and left hepatic ducts, can be unilobar or bilobar, and show an increased tendency for affliction of the left lobe.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which hepatolithiasis develops has yet to be fully elucidated. Studies have suggested that cholestasis, cholangitis, an anatomical abnormality of the bile ducts, abnormal bile metabolism, malnutrition, and low socio-economic status are risk factors for hepatolithiasis (5,6). The incidence of hepatolithiasis may decrease in areas where the condition is prevalent because people in those areas have adopted a Western diet.…”
Section: Introductionmentioning
confidence: 99%
“…Sites for possible hidden stones are numerous and are described below (Figure ): Cystic duct Hartmann's pouch with Mirizzi syndrome is a potential complication. In these cases, stones in the Hartmann's pouch compress the common hepatic duct, leading to the development of cholangitis Intrahepatic duct stones, occurring more commonly in Asian populations, are frequently associated with biliary strictures, primary sclerosing cholangitis, choledochal cysts, and biliary tract tumors.…”
mentioning
confidence: 99%
“…However, roughly 10% of individuals with intrahepatic stones have spontaneous occurrence in the setting of anatomic variation and poor biliary evacuation. For instance, the left hepatic duct is slender and meets the common hepatic duct at nearly a right angle, making it more susceptible to sludging and biliary stone formation Anatomical variations of the CBD may result in large lumen bile ducts with residual remains of stones that are not easily visualized …”
mentioning
confidence: 99%